Indian Contribution to Artificial Intelligence in the Field of Social Sciences during 2014 - 2023 - Parmar, Seema; Pateria, Rajive; Kumari, Dinesh; Shallu (DESIDOC Journal of Library & Information Technology, 2024)
The present study intends to identify and analyse the Indian research output on AI in the field of social sciences from 2014 to 2023. This paper showcases the publication types, yearly distribution of publications, prolific authors and preferred sources for publications; highlights contributing institutions and collaborating countries. The data source is the ‘Scopus’ database, refining through key terms and different filters. The findings of the study emphasise Indian authors’ contributions, listing of top authors, and continuous increase in AI publications and citations with occasional fluctuations. Indian writers are remarkably productive, especially those from universities such as the Symbiosis Institute of Technology and Uttranchal University Dehradun. The leading affiliation in contributing research on AI is Symbiosis International Deemed University in terms of citations and publications, while the leading collaborative countries are the United States, the United Kingdom, Saudi Arabia, and China.